The Formation of Human Arteriovenous Malformation Organoids and Their Characteristics - Eun Jung Oh; Hyun Mi Kim; Suin Kwak; Chanhoe Huh; Ho Yun Chung (Cells)
Arteriovenous malformations (AVMs) are characterized by direct connections between arteries and veins without intervening capillaries, with the concomitant formation of abnormal vascular networks associated with angiogenesis. However, the current understanding of the diagnosis and treatment of AVMs is limited, and no in vitro disease models exist at present for studying this condition. In this study, we produced endothelial cells (ECs) in two-dimensional cultures and three-dimensional (3D) blood vessel organoids (BVOs), comparing gene expression profiles between normal and AVM organoids. The normal and AVM organoids were examined via immunofluorescence staining using CD31 and phalloidin. The AVM organoids showed significantly higher expression levels of CD31 and phalloidin than the normal organoids. Genes such as FSTL1, associated with angiogenesis, showed significantly higher expression in the AVM organoids than in the normal organoids. In contrast, the MARCKS gene exhibited no significant difference in expression between the two types of organoids. The capillaries and related CSPG4 genes exhibited the lowest expression in the 3D AVM organoids. Furthermore, hsa-mir-135b-5p, a small RNA related to AVMs, showed elevated expression in AVM tissues and significantly higher levels in 3D AVM organoids. In our study, we were able to successfully establish AVM organoids (hBVOs) containing ECs and mural cells through advancements in stem cell and tissue engineering. These organoids serve as valuable models for investigating disease mechanisms, drug development, and screening potential therapeutic interventions in drug discovery. These findings contribute essential insights for the development of treatment strategies targeting AVMs.